The Innovation Model for Small and Medium Enterprises in Thailand - et. al., Araya Uengpaiboonkit, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to 1) to study the elements of the innovation model for small and medium enterprises in Thailand 2) to develop the model of the innovation model for small and medium enterprises in Thailand. There are 3 steps of research: 1) study documents and related research. 2) Develop a model for the innovation of small and medium enterprises in Thailand with questionnaire from manager of small and medium enterprises 400 persons 3) analyzed the elements of the development pattern of the innovation model for small and medium enterprises in Thailand by analyzing the elements; The statistics used for data analysis were percentage, range, quartile, mean, standard deviation and elemental analysis. Research findings showed that 1) The study of the innovation model for small and medium enterprises in Thailand found that it consisted of 3 important components: product innovation, process innovation, market innovation of the innovation model for small and medium enterprises in Thailand. 2) Development of the innovation model for small and medium enterprises in Thailand found that there are 5 main components: dynamic capabilities, market orientation, intellectual capabilities, innovation, competitive advantage. The innovation model for small and medium enterprises in Thailand overall and the aspects are good.